(untitled) (Architecture Image Studies, 2025)
Industrialization and urbanization have their own consequences. Industries using not environmentally friendly machines certainly pollute the air and water. The industries located in and around Agra City in Uttar Pradesh State, India, are causing air pollution, and its impact has been witnessed on the beauty of the Taj Mahal. The Taj Mahal is a historical heritage monument that is considered a pride of India. Industries located in the Taj Trapezium Zone (TTZ), such as oil refineries, foundries, glass works, brick kilns, and tanneries, dump garbage into the Yamuna River, adding to it automobile smoke which is causing acid rain in and around the Taj Mahal, resulting in corrosion on marble, black patches, and white marble turning yellow color. The Taj Mahal is recognized as a heritage structure by UNESCO and the Archeological Survey of India (ASI). Millions of visitors from around the world flock to the Taj Mahal to see its architectural beauty. A Public Interest Litigation (PIL) was filed by M.C. Mehta, advocate, before the Supreme Court of India to pass directions to the appropriate authorities for preservation of the beauty of the Taj Mahal. The court monitored the case for several years and directed the 292 industries to change from the use of coal and carbon fuels to natural gas, and the industries not willing to follow the directions were ordered to relocate from the TTZ area. The study recommends that development must be sustainable and eco-friendly to preserve nature, natural resources, and archaeological sites.